How implicit self-theories and dual-brand personalities enhance word-of-mouth. (11th January 2021) - Mandal, Sudipta; Sahay, Arvind; Terron, Adrian; Mahto, Kavita
Abstract : Purpose: Consumers subscribe to different mindsets or implicit theories of personality malleability, namely, fixed and growth mindsets. This study aims to investigate how and why consumers' mindsets can influence their word-of-mouth (WOM) intentions toward a brand and the consequent implications for a brand's personality. Design/methodology/approach: Three mall-intercept studies and one online study demonstrate the influence of consumers' fixed and growth mindsets on their WOM intentions. The first two mall-intercept studies identify motivations underlying consumers' WOM intentions as a function of their mindset orientations. The third mall-intercept study examines the implications of such mindset-oriented WOM intentions for a brand's personality dimension and the underlying psychological mechanism. The fourth study tests the link between WOM intent and behavior. Findings: Results show that fixed (growth) mindset individuals exhibit greater WOM intentions than growth (fixed) mindset individuals for motives of "impression management" ("learning and information acquisition"). Findings further demonstrate that brands that exhibit dual personality dimensions simultaneously, one salient and the other non-salient at any instant, garner equivalent WOM intentions from both fixed and growth mindset individuals, contingent on the fit between the salient brand personality dimension and the dominant consumer mindset. Finally, using a real brand, it can be seen that WOM intentions actually translate into behavior. Research limitations/implications: The study measures offline WOM intent but not offline WOM behavior. Practical implications: This study sheds new light on branding strategy by demonstrating how and why dual-brand personalities may attract consumers with both kinds of implicit self-theory orientations. Relatedly, it also demonstrates a technique of framing ad-appeals that support the dual-brand personality effect. Originality/value: To the best of the authors' knowledge, this is the first study to propose and demonstrate the use of simultaneous dual-brand personalities as an optimal branding strategy.